Cross-cultural narratives of weaponised artificial intelligence: Comparing France, India, Japan and the United States - Ingvild Bode; Hendrik Huelss; Anna Nadibaidze; Tom FA Watts (Big Data & Society)
Stories about ‘intelligent machines’ have long featured in popular culture. Existing research has mapped these artificial intelligence (AI) narratives but lacks an in-depth understanding of (a) narratives related specifically to weaponised AI and autonomous weapon systems and (b) whether and how these narratives resonate across different states and associated cultural contexts. We speak to these gaps by examining narratives about weaponised AI across publics in France, India, Japan and the US. Based on a public opinion survey conducted in these states in 2022–2023, we find that narratives found in English-language popular culture are shared cross-culturally, although with some variations. However, we also find culturally distinct narratives, particularly in India and Japan. Further, we assess whether these narratives shape the publics’ attitudes towards regulating weaponised AI. Although respondents demonstrate overall uncertainty and lack of knowledge regarding developments in the sphere of weaponised AI, they assess these technologies in a negative-leaning way and mostly support regulation. With these findings, our study offers a first step towards further investigating the extent to which weaponised AI narratives circulate globally and how salient perceptions of these technologies are across different publics.